Hurdling vs flat running in the preparation of Poland`s best 110-m and 400-m hurdlers - Iskra. J.; Walaszczyk, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: A change in training load is one of the most important factors in the improvement of sport results. In both hurdle distances (110m H and 400m H), for males, the core of the preparation is running distance: with hurdles (so called "rhythm") and flat (sprint and special endurance) (Iskra, 1991; Ward-Smith, 1997; Iskra et al., 2006). The main aim of this study was to find differences in special (hurdle rhythm) and directed (flat running) training loads on groups of 110m and 400m hurdlers. Athletes at different skill levels in the sport of hurdling were also examined. Methods Poland`s best hurdlers from the period 1994-2006 (n=68; body height=184.6±4.2 cm, body weight= 75.7±5.1 kg) participated in the study. The athletes were separated into four groups, divided according to distance (110m H - "high" hurdlers/HH; n=33, and 400m H - "intermediate" hurdlers/IH; n=35) and sport level (Poland`s best hurdlers/BH and club level athletes/CH). To estimate running loads in an annual training program the research separated three flat running skills (maximum speed (0-to 60m), speed endurance (60-150m) and special endurance (150-500m). All runs were practiced at maximal and submaximal speeds. For the special (=hurdle, = rhythm) runs we included short (volume hurdles on distance - 1-3), middle (4-7 hurdles) and long (8-11)"rhythms" (Iskra 1991, McFarlane 2004). To examine the differences between the four groups (HH, IH, BH, CH) we used one-way analysis of variance (ANOVA) with final Tuckey`s test. Results There were no significant differences between speed preparation for all groups (F=2.35, p 0.05). In the case of speed and special endurance the findings indicated statistical differences between groups HH and IH (respectively p 0.05 and p 0.01). In the annual 400m H preparation program, intermediate hurdlers ran 11.8±5.0 km speed-endurance distances (110m H - 8.9±2.9 km), four times more than HH distances for the special endurance. Differences were significant between hurdlers in groups of various sport level and hurdle rhythm between the 4th and 7th hurdles and so called "long rhythm" - over 8th hurdle (p 0.001). Conclusions Success in hurdles depends on special (hurdle) training in middle and long distances (over 4th hurdle). This is important information for coaches specializing in both types of (110m and 400m H) hurdles coaching.